Fatigue Life Analysis of Mooring System: The Effect of Asymmetry Mooring System Configuration on Single Point Mooring - Eko Budi Djatmiko; Murdjito Murdjito; Revy Maghriza (International Journal of Offshore and Coastal Engineering, 2021)
This journal explains the fatigue life analysis of anchor chain in the stand-alone single point mooring by comparing the 4x1 asymmetric and symmetrical mooring system configurations to determine whether the effect of the asymmetrical mooring system configuration on the fatigue life of the anchor chain is related to the length of the mooring lines, the pretensions of the mooring lines, and the angle of spread. The analysis was reviewed on the condition of ULS and FLS environmental loading based on API RP 2 SK code using Orcaflex with 3 hours of time- domain simulation. In the ULS condition, the symmetrical configuration can withstand environmental loads better in the direction of 0o and 180o with the generated maximum tension and maximum offset value smaller than the result from asymmetrical configuration. While the asymmetrical configuration can withstand environmental loads better in the direction of 90o and 270o with the generated maximum tension and maximum offset value smaller than the result from symmetrical configuration. In the FLS condition, the asymmetrical configuration has a longer minimum fatigue life and design life of anchor chain than the symmetrical configuration. This happens because of the spread angle of the mooring line, the length of the mooring line, and the pretension of the mooring line